Activated Charcoal Magnetic Composite from Jengkol Peels as An Efficient Adsorbent for Aquatic Antibiotic Removal: An in Vitro Study - Wardani, Gatut Ari; Nurhidah, Mia; Wulandari, Winda Trisna; Nofiyanti, Estin; Syahputra, Ricky Andi; Indra, Indra (Universitas Jenderal Soedirman, 2024)
Antibiotic resistance has become a global issue that is quite worrying because it can threaten the survival of living things, especially humans. This resistance can occur due to the inappropriate use of antibiotics by the community. This study aims to determine the ability of activated charcoal magnetic composites (ACMC) to adsorb tetracycline hydrochloride compounds. Samples were obtained from jengkol peel waste which was charred and activated using acid and the addition of magnetic properties. The more PbFe2O4 added to activated charcoal, the greater the magnetic properties, surface area, pore-volume, and pore radius. The results showed that a type of IV adsorption isotherm which is a characteristic of mesoporous materials with a pore size of 2.0892 nm. The addition of magnetic properties to activated charcoal increase 29.33% the amount of tetracycline that is adsorbed by the adsorbent with optimal absorption in alkaline conditions. The adsorption process followed the adsorption kinetics of Ho and the Freundlich adsorption isotherm with an adsorption capacity of 76.3359 mg/g. ACMC material can potentially be one of the adsorbents that can reduce contamination of tetracycline hydrochloride antibiotics in the aquatic environment so that antimicrobial resistance can be minimized. Keyword: acidity, agricultural waste, carbonization, functional Group, VSM analysis